Solid Waste Management in Small Island Destinations: A Case Study of Gili Trawangan, Indonesia - Willmott, Lacey; Graci, Sonya (Téoros, 2012)
Solid waste management is a critical, complex, multi-dimensional challenge for societies. The nature of solid waste management in each community can differ based upon a number of factors including economic activities and geographies. Solid waste management in small island tourist communities is often complicated by their isolated geographies and tourism dominated economies, resulting in even greater challenges for ensuring sustainable solid waste management. This article discusses a case study of the small tourist island of Gili Trawangan, Indonesia that has addressed their long-standing issues of solid waste management through a governance and management approach centered on a multi-stakeholder partnership. The partnership involves collaboration between a community-based organization and environmental non-governmental organization, each having broader ties to stakeholders in the island community. Through this partnership they have seen improvements with stakeholder involvement, access to resources, financial support, transparency and accountability, and have been able to implement a number of key initiatives to improve waste management in this destination and move towards sustainability. Initiatives include source separation, expansion of collection services, revised collection fees, material reuse projects, education and awareness initiatives and enhanced planning.